Introduction: Drama and Conversion - Wittek, Stephen (Early Theatre, 2025)
This introduction presents a new collection of essays examining the role of conversion in early modern English drama. Together, the contributions demonstrate how the theatre served as a space for dramatizing the political, theological, and psychological complexities of identity transformation. With case studies ranging from city comedy to colonial propaganda, the volume emphasizes conversion’s entanglement with race, gender, and performance. Drawing on recent scholarship, the authors highlight drama’s unique capacity to stage conversional doubt, sincerity, and dissimulation — establishing theatre as both a site of ideological reinforcement and a medium for interrogating the limits of belief and belonging.